66-m-8=0

Simple and best practice solution for 66-m-8=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 66-m-8=0 equation:


Simplifying
66 + -1m + -8 = 0

Reorder the terms:
66 + -8 + -1m = 0

Combine like terms: 66 + -8 = 58
58 + -1m = 0

Solving
58 + -1m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-58' to each side of the equation.
58 + -58 + -1m = 0 + -58

Combine like terms: 58 + -58 = 0
0 + -1m = 0 + -58
-1m = 0 + -58

Combine like terms: 0 + -58 = -58
-1m = -58

Divide each side by '-1'.
m = 58

Simplifying
m = 58

See similar equations:

| n+10+6n=2(10-11n)-4(7-7n) | | x^2+2-4=0 | | 2(x-4)=3(x+9) | | W+7-1=-6 | | -10(6b-5)=-198 | | 5w-2=2w+10 | | -38-12x=-9x+46 | | -2x+1=-21 | | 5(4-3j)=-2(3j-5) | | 11x(12-4)=616 | | .5(x-3)=.25(x+1) | | -18-4= | | n-(8+4n)=2(3n-4) | | -(-x-1)=4x-5-3x | | 3x^2-8=155 | | 5x-49=9x+23 | | 11(12-4)=616 | | 64x^2-96x+36=0 | | -2(b+5)+7(6+b)= | | 9(9-x)=4x-10 | | 11(12x-4)=616 | | -3x=x+6+2x | | x(8x+7)=3x^2-2x+18 | | 2=9b-11b | | 3(x+6)=5(x+2) | | -(z+12)=5(2z-1) | | 6(2d-1)+13-19= | | 15y-9y-12+3= | | 2(5t-3)=-2(t+3) | | -5x-143=130+8x | | -6x-4(-3x+18)=-132 | | 74-1.5x+1.5x-2=72 |

Equations solver categories